Understanding Fiduciary Duties and Relationship Fiduciarity - Rotman, Leonard (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2017)
How well do we truly understand the legal concepts we regularly use and discuss? Truly understanding a legal concept necessitates understanding why it exists, what it was constructed to accomplish, and the purpose or purposes it was intended to facilitate. A lack of attentiveness to that raison d’être results in the loss of connection between the concepts and their underlying rationales. The divorce between legal concepts and their philosophical foundations renders the former susceptible to manipulation and misuse as they lose their connection to their philosophical and doctrinal foundations and subsequently become more and more unintelligible.As it presently sits, fiduciary jurisprudence is one of the most confused and least understood areas of contemporary law. This is not a new development, but one of long standing. Jurisprudence and legal commentary indicate that both lawyers and judges misuse fiduciary principles for reasons inconsistent with fiduciary law’s conceptual foundation.The primary purpose of this article is to enhance the understanding of fiduciary duties and relationship fiduciarity by promoting a more robust understanding of the fiduciary concept centred upon its foundational raison d’être. In the process of establishing a stronger philosophical and doctrinal base for the fiduciary concept, the article will also contemplate the contributions provided by of one of the more recent additions to fiduciary law scholarship, authored by Remus Valsan and published in a recent issue of this same law journal.